Imaging and therapeutic applications of zinc(II)-dipicolylamine molecular probes for anionic biomembranes - Rice, Douglas R. (Chem Commun (Camb), 2016)
This feature article describes the development of synthetic zinc(II)-dipicolylamine (ZnDPA) receptors as selective targeting agents for anionic membranes in cell culture and living subjects. There is a strong connection between anionic cell surface charge and disease, and ZnDPA probes have been employed extensively for molecular imaging and targeted therapeutics. Fluorescence and nuclear imaging applications include detection of diseases such as cancer, neurodegeneration, arthritis, and microbial infection, and also quantification of cell death caused by therapy. Therapeutic applications include selective targeting of cytotoxic agents and drug delivery systems, photodynamic inactivation, and modulation of the immune system. The article concludes with a summary of expected future directions.